2011
DOI: 10.1210/jc.2011-1426
|View full text |Cite
|
Sign up to set email alerts
|

GDC-0941 Inhibits Metastatic Characteristics of Thyroid Carcinomas by Targeting both the Phosphoinositide-3 Kinase (PI3K) and Hypoxia-Inducible Factor-1α (HIF-1α) Pathways

Abstract: PI3K plays a prominent role in the metastatic behavior of thyroid carcinoma cells irrespective of O(2) tension and appears upstream of HIF activation. GDC-0941 significantly inhibited the metastatic phenotype, supporting the clinical development of PI3K inhibition in thyroid carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 26 publications
1
48
0
1
Order By: Relevance
“…HIF1 induces expression of VEGF, a growth factor, and MET, an oncogene, which are also upregulated in thyroid tumors as compared to normal thyroid tissues [162]. On the other hand, PI3K-AKT and MAPK increase expression of HIF1 in thyroid tumor [161,164,165] while a mutation in BRAF (V600E) also affects expression levels of HIF1␣ in papillary thyroid cancer [165]. Interestingly, inhibition of expression levels of HIF-1␣ and HIF-2␣ by GDC-0941 in four different thyroid tumor cells (BcPAP, WRO, FTC133, and 8505c) resulted in inhibition of VEGF secretion [166].…”
Section: The Hif1α Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…HIF1 induces expression of VEGF, a growth factor, and MET, an oncogene, which are also upregulated in thyroid tumors as compared to normal thyroid tissues [162]. On the other hand, PI3K-AKT and MAPK increase expression of HIF1 in thyroid tumor [161,164,165] while a mutation in BRAF (V600E) also affects expression levels of HIF1␣ in papillary thyroid cancer [165]. Interestingly, inhibition of expression levels of HIF-1␣ and HIF-2␣ by GDC-0941 in four different thyroid tumor cells (BcPAP, WRO, FTC133, and 8505c) resulted in inhibition of VEGF secretion [166].…”
Section: The Hif1α Pathwaymentioning
confidence: 99%
“…On the other hand, PI3K-AKT and MAPK increase expression of HIF1 in thyroid tumor [161,164,165] while a mutation in BRAF (V600E) also affects expression levels of HIF1␣ in papillary thyroid cancer [165]. Interestingly, inhibition of expression levels of HIF-1␣ and HIF-2␣ by GDC-0941 in four different thyroid tumor cells (BcPAP, WRO, FTC133, and 8505c) resulted in inhibition of VEGF secretion [166]. Koperek et al demonstrated that tumor hypoxia is involved in the development of regional metastases in MTC [167].…”
Section: The Hif1α Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of this inhibition is solely dependent upon the hypoxia-inducible factor-1α (HIF-1α). It has also been suggested that the anti-proliferative effects of GDC-0941 depend on PTEN status in thyroid cancer [72] , but the mechanism is still unclear. Thus, the role of PTEN status in the effectiveness of GDC-0941 is distinct for different cancer types.…”
Section: Achievements In Clinical Trialsmentioning
confidence: 99%
“…A second positive regulatory pathway has been described for PI3K/mTOR that is involved in regulating Hif-1 protein synthesis through AKT/PKB (protein kinase B), mTOR (mammalian target of rapamycin) and S6K (p70 S6 kinase) [448]. It has recently been demonstrated that the PI3K inhibitor GDC-0941 represses Hif1 and Hif-2 expression and activity [449].…”
Section: The -Catenin Tcf/lef Transcription Complexmentioning
confidence: 99%